Mecanismos de inflamación en conjuntivitis alérgica aguda en niños, años: 2016 al 2021 (2021)
The present study is part of a descriptive investigation, which allows highlighting the mechanisms of inflammation in acute allergic conjunctivitis. Objective: To present the mechanisms of inflammation in acute allergic conjunctivitis in children. Methodology: This work was carried out through a bibliographic review and databases available in the virtual library of the Antonio Nariño University were used PubMed, Science Direct, Springer link, Scopus, web of science between the years 2016 and 2021 and yielded a total of 347 articles in the last 5 years, which passed 22 according to the inclusion criteria. Results: Different filters was made in excel in each database, the first filter was articles from the last five years, the second filter was articles that was Full Text, and the third filter were articles related to the topic of "inflammation mechanisms "Or" risk factors associated with allergic conjunctivitis.